2017
DOI: 10.1021/acsami.7b04323
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Effects of Materials on Bio-Interfaces

Abstract: Electrical stimulation of cells and tissues is an important approach of interaction with living matter, which has been traditionally exploited in the clinical practice for a wide range of pathological conditions, in particular, related to excitable tissues. Standard methods of stimulation are, however, often invasive, being based on electrodes and wires used to carry current to the intended site. The possibility to achieve an indirect electrical stimulation, by means of piezoelectric materials, is therefore of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 132 publications
1
83
0
Order By: Relevance
“…It has also been shown that in case of neuronal, cells calcium ionic pathways play key role in controlling the differentiation of cells exposed to piezoelectric stimulation [225]. To gain a better understanding of the interactions and provide more quantitative assessment of the processes involved, it has also been highlighted that modelling and simulation of piezoelectric materials can be a helpful tool [226]. [140,227] .…”
Section: Biological Performance Of Piezoelectric Materialsmentioning
confidence: 99%
“…It has also been shown that in case of neuronal, cells calcium ionic pathways play key role in controlling the differentiation of cells exposed to piezoelectric stimulation [225]. To gain a better understanding of the interactions and provide more quantitative assessment of the processes involved, it has also been highlighted that modelling and simulation of piezoelectric materials can be a helpful tool [226]. [140,227] .…”
Section: Biological Performance Of Piezoelectric Materialsmentioning
confidence: 99%
“…Furthermore, low-intensity and low-frequency alternating current (AC) stimulation resulted able to significantly enhance the effects of chemotherapy for the treatment of glioblastoma in clinical trials 12 . Specifically, AC not only is able to affect cancer cell proliferation without the use of any drugs, yet also reduce multidrug resistance by impairing the plasma membrane translocation of MDR1, a P-glycoprotein (P-gp) the overexpression of which is associated to chemotherapy resistance 13 . Nevertheless, AC stimulation can also affect the proliferation of non-malignant cells ( i.e ., human astrocytes) 10 and, for this reason, the specific and targeted delivery of electric stimuli just to cancer cells is of extreme importance.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric nanomaterials have shown to be a very promising tool for a wireless, non-invasive, and targeted electric stimulation of cells and tissues 13 . When these nanomaterials undergo mechanical deformations, they are able to generate electric potentials on their surface thanks to the direct piezoelectric effect.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive nanostructures that have been used for the treatment of various diseases can respond to physical stimuli, including ultrasounds, light, electric fields, and magnetic fields (Mura et al, 2013 ; Marino et al, 2015 , 2017b , c ; Genchi et al, 2016 , 2017b ), or they can take advantage of the changes in the biological microenvironment of each disease and respond to alterations in temperature, pH, redox conditions, ROS, and enzyme concentration (Tapeinos et al, 2008 , 2017 ; de la Rica et al, 2012 ; Torchilin, 2014 ; Tapeinos and Pandit, 2016 ; Bizeau et al, 2017 ). Furthermore, a combination of these stimuli (Mura et al, 2013 ; Tapeinos et al, 2013 , 2016 ; Efthimiadou et al, 2014a , b ; Lu et al, 2016 ) have also been used to increase the therapeutic versatility of the MDDS.…”
Section: Multifunctional Drug Delivery Systems (Mdds)mentioning
confidence: 99%